Rehabilitate those who care - Andreia Magalhães; Daniela Chamusca; Isabel Leitão; Joana Capelo; Mariana Silva; Virginia Pereira (Associação Portuguesa dos Enfermeiros de Reabilitação, 2021)
Introduction: Musculoskeletal Injuries are often related to the exercise of the profession in the health field. Labor Gymnastics is considered as a method capable of preventing these injuries and promoting the general well-being of workers. Objective: Analyze the results of Labor Gymnastics on health professionals from a service in a hospital center in northern Portugal in preventing labor-related musculoskeletal injuries. Methodology: It was used a observational cohort study, by means of self-completed questionnaires, with subsequent analysis and verification of frequencies and calculation of central tendency and dispersion measures. Results: Increased willingness and motivation to work, promoting well-being at work, fostering team spirit and concern with adopting correct postures are the benefits most mentioned by professionals. Most workers believe that Labor Gymnastics has played an important role in pain relief. Conclusion: The implementation of the regular practice of Labor Gymnastics in hospital services lead to health gains for workers in many ways.